Nature (excerpt) - Emerson, Ralph Waldo (Problemos, 2016)
Versta iš: Ralph Waldo Emerson, Nature,Boston: James Munroe and Company, 1836, pp. 76–81 (Chapter VII ‘Spirit’).Iš anglų kalbos vertė Ruslanas Baranovas, Marius Jakštas, Vaida Kalkauskaitė,Kęstas Kirtiklis, Živilė Pabijutaitė, Viktorija Ringytė, Andrius Šimašius, Vytautas Šliuburys, Vytautas Vyšniauskas